Design, Synthesis and Biological Evaluation of Novel Primaquine-Cinnamic Acid Conjugates of the Amide and Acylsemicarbazide Type - Kristina Pavić; Ivana Perković; Petra Gilja; Filip Kozlina; Katja Ester; Marijeta Kralj; Dominique Schols; Dimitra Hadjipavlou-Litina; Eleni Pontiki; Branka Zorc (Molecules, 2016)
In this paper design and synthesis of a scaffold comprising primaquine (PQ) motif and cinnamic acid derivatives (CADs) bound directly (compounds 3a–k) or via a spacer (compounds 7a–k) are reported. In the first series of compounds, PQ and various CADs were connected by amide bonds and in the second series by acylsemicarbazide functional groups built from the PQ amino group, CONHNH spacer and the carbonyl group originating from the CADs. PQ-CAD amides 3a–k were prepared by a simple one-step condensation reaction of PQ with a series of CAD chlorides (method A) or benzotriazolides 2 (method B). The synthesis of acylsemicarbazides 7a–k included activation of PQ with benzotriazole, preparation of PQ-semicarbazide 6 and its condensation with CAD chlorides 4. All synthesized PQ-CAD conjugates were evaluated for their anticancer, antiviral and antioxidative activities. Almost all compounds from series 3 were selective towards the MCF-7 cell line and active at micromolar concentrations. The o-fluoro derivative 3h showed high activity against HeLa, MCF-7 and in particular against the SW 620 cell line, while acylsemicarbazide 7f with a benzodioxole ring and 7c, 7g and especially 7j with methoxy-, chloro- or trifluoromethyl-substituents in the para position showed high selectivity and high inhibitory activity against MCF-7 cell line at micromolar (7c, 7f, 7g) and nanomolar (7j) levels. Acylsemicarbazide derivatives with trifluoromethyl group(s) 7i, 7j and 7k showed specific activity against human coronavirus (229E) at concentrations which did not alter the normal cell morphology. The same compounds exerted the most potent reducing activity in the DPPH test, together with 7d and 7g, while methoxy (compounds 7c–e), benzodioxole (7f), p-Cl (7g) and m-CF3 (7i) acylsemicarbazides and amide 3f presented the highest LP inhibition (83%–89%). The dimethoxy derivative 7d was the most potent LOX inhibitor (IC50 = 10 μΜ). The performed biological tests gave evidence of acylsemicarbazide functional group as superior binding group in PQ-CAD conjugates.